2014
DOI: 10.1186/1471-2164-15-383
|View full text |Cite
|
Sign up to set email alerts
|

Organellar genomes of the four-toothed moss, Tetraphis pellucida

Abstract: BackgroundMosses are the largest of the three extant clades of gametophyte-dominant land plants and remain poorly studied using comparative genomic methods. Major monophyletic moss lineages are characterised by different types of a spore dehiscence apparatus called the peristome, and the most important unsolved problem in higher-level moss systematics is the branching order of these peristomate clades. Organellar genome sequencing offers the potential to resolve this issue through the provision of both genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…However, this small size does not interfere with the G + C content, which is high. The plastid genomes of the closest Polytrichum species have a GC percentage of 28% to 33% [21,22] and those of seed plants range between 34% and 40% [50]. Cai et al, observed high G + C contents in the chloroplast coding regions, and certain regions had higher percentages than others, such as the IR region with its four genes with high levels of G and C [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this small size does not interfere with the G + C content, which is high. The plastid genomes of the closest Polytrichum species have a GC percentage of 28% to 33% [21,22] and those of seed plants range between 34% and 40% [50]. Cai et al, observed high G + C contents in the chloroplast coding regions, and certain regions had higher percentages than others, such as the IR region with its four genes with high levels of G and C [51].…”
Section: Discussionmentioning
confidence: 99%
“…The genome contains a total of 62 genes, including 2 rRNA genes as in P. juniperinum (1 rnl and 1 rns), 19 tRNAs, 3 rRNAs, 3 ORFs (ORF533, ORF622, and ORF187), 13 protein-coding genes related to mitochondrial oxidative metabolism, and 13 ribosomal proteins (4 rpl and 9 rps). The rps10 gene that encoded a protein from the 40S subunit of the ribosome was not found in Antarctic Polytrichaceae, apparently that region was lost before the split of mosses lineage since this absence is also evident in Tetraphidaceae [21] and Funariaceae [24]. The nad7 pseudogene in Marchantia polymorpha and ORF187 is frequently observed in the mtDNA of M. polymorpha [25] and contradictorily does not occur in Tetraphis pellucida but seems to be present in the Polytrichum species studied ( Table 2).…”
Section: Figure 1 Blast Ring Image Generator Output Image Of the Chlmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the gene content in the inverted repeats of both these species were found identical. Due to an increased total length of intragenic spacer regions in the large single copy region of the Tetraphis pellucida chloroplast genome, it is ~5 kb longer than those of Syntrichia ruralis and Physcomitrella patens (Bell et al, 2014).…”
Section: Tetraphis Pellucida Hedw (Bryophyta)mentioning
confidence: 99%
“…Recently, Bell et al (2014) published the chloroplast genome sequence of Tetraphis pellucida. It was downloaded from NCBI in FASTA and GenBank format (NC_024291, 127489bp).…”
Section: Tetraphismentioning
confidence: 99%